Monitoring System for Distribution Box Power Trips - Ainul Jamilus, Mohammad Alif Asraff; Maizul Ishak (Progress in Engineering Application and Technology, 2024)
This project introduces a Monitoring System for Distribution Box Power Trips utilizing the ESP32 Devkit and Blynk platform. The system is designed to provide real-time monitoring and control of Miniature Circuit Breakers (MCBs) in distribution boxes. By leveraging the ESP32 Devkit’s capabilities and Blynk’s user-friendly interface, the system aims to enhance the reliability and efficiency of power distribution networks. The project involves developing a comprehensive monitoring system that can detect power trips, manage electrical parameters, and implement automated control mechanisms to prevent disruptions. Through the integration of ESP32 Devkit and Blynk, this project showcases a practical solution for optimizing power distribution infrastructure and ensuring operational safety.